2015
DOI: 10.4149/bll_2015_121
|View full text |Cite
|
Sign up to set email alerts
|

Iloprost and vitamin C attenuates acute myocardial injury induced by suprarenal aortic ischemia-reperfusion in rabbits

Abstract: OBJECTIVE: The aim of this study was to evaluate antioxidant and cytoprotective effects of iloprost and Vitamin C in a distant organ after abdominal aorta ischemia-reperfusion injury. MATERIAL AND METHODS: Twenty-eight New Zealand rabbits weighing 2,400-2,800 g were used for this study. The rabbits were divided into four equal groups. These groups are control group, sham group, iloprost group, and iloprost + vitamin C group. Suprarenal aorta was occluded with a vascular clamp. Following 30 minutes of ischemia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…In this study we found that NO level was significant decreased after IRI but NO level and renal function were improved by vitamin C supplementation. Our results are in agreement with previous reports demonstrating that vitamin C has protective effects on tissues with IRI [22,[37][38][39]. In addition, our findings also showed that vitamin C administration elevated GSH level after renal ischemic injury.…”
Section: Discussionsupporting
confidence: 83%
“…In this study we found that NO level was significant decreased after IRI but NO level and renal function were improved by vitamin C supplementation. Our results are in agreement with previous reports demonstrating that vitamin C has protective effects on tissues with IRI [22,[37][38][39]. In addition, our findings also showed that vitamin C administration elevated GSH level after renal ischemic injury.…”
Section: Discussionsupporting
confidence: 83%
“…Cellular pathophysiologic mechanisms underlying myocardial and lung I/R injuries are diverse, including ion accumulation, dissipation of mitochondrial membrane potential, increased ROS formation, apoptosis and/or autophagy, immune activation and neutrophil infi ltration, and endothelial dysfunction (25). Since the reason behind the I/R injury in the heart and lung is complex, interventions require a spectrum of targets, mainly in the antioxidant and anti-infl ammatory pathways (26)(27)(28)(29). The generation of free radicals, especially in the fi rst few minutes of myocardial and lung reperfusion can harm cellular lipids, proteins, and nucleic acids and ultimately lead to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Iloprost may stimulate the release of endogenous tissue plasminogen activator or counteract its inhibitory effects [ 35 ]. Iloprost reduces vasoconstriction induced by thromboxane A2 [ 36 ], and may reduce oxidative stress from free radicals, moderating reperfusion injury [ 37 , 38 ]. The effect on platelet aggregation may be reversed within two hours), but prostacyclin effects may disrupt the vicious cycle of activated platelets and leukocytes that damages endothelium [ 35 , 39 ].…”
Section: Discussionmentioning
confidence: 99%